Adenoid cystic carcinoma of the breast in a male: A case report. Issue 32 (August 2019) - Pang, Wenyang; Wang, Zhengyi; Jin, Xiaoyan; Zhang, Qiang
Abstract: Rationale: Adenoid cystic carcinoma (ACC) of the breast is an infrequent neoplasm, and the occurrence in males is rare. Therefore, diagnostic and therapeutic challenges are inevitable. Patient concerns: Herein, we present a case of a 44-year-old man with a tumor on his right breast that he had known about for 6 years. Diagnoses: The patient underwent a lumpectomy, and the histological examination confirmed a diagnosis of ACC. Interventions: Modified radical mastectomy was subsequently conducted in the patient. No positive lymph nodes were observed in the postoperative pathological examination. Following the surgery, the patient received adjuvant chemotherapy. Outcomes: The patient remained recurrence-free at 26 months. Lessons: Compared to female breast ACC, male breast ACC may behave differently biologically and have a different prognosis. Our case will provide more diagnostic and treatment experience to deal with this disease.